2015
DOI: 10.3174/ajnr.a4284
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Dynamic Susceptibility Contrast-Enhanced and Diffusion-Weighted MR Imaging in Patients with Glioblastomas

Abstract: BACKGROUND AND PURPOSE: Prediction of survival in patients with glioblastomas is important for individualized treatment planning. This study aimed to assess the prognostic utility of presurgical dynamic susceptibility contrast and diffusion-weighted imaging for overall survival in patients with glioblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 43 publications
3
22
0
Order By: Relevance
“…This is further supported by the observation that hypo-perfusion (as seen in pattern 3), previously reported to be a marker for better clinical out-come in glioma [15], correlates with high-grade meningiomas with poor prognosis. Angiogenesis in both meningioma and glioma is known to share a common signaling pathway mediated by vascular endothelial growth factor (VEGF) [16,26,27].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This is further supported by the observation that hypo-perfusion (as seen in pattern 3), previously reported to be a marker for better clinical out-come in glioma [15], correlates with high-grade meningiomas with poor prognosis. Angiogenesis in both meningioma and glioma is known to share a common signaling pathway mediated by vascular endothelial growth factor (VEGF) [16,26,27].…”
Section: Discussionsupporting
confidence: 73%
“…Perfusion, diffusion and MR spec-troscopy have all been investigated as potential methods to add value to standard imaging in the assessment of meningiomas [12]. Most perfu-sion studies of central nervous system tumors have focused on the use of quantitative parameters, such as rCBV and CBF, as markers of histo-pathological grade, therapy response and clinical outcome [1315]. In the present study, a qualitative examination of CBF maps was conducted in a patient cohort with meningioma, and its potential for predicting meningioma tumor grade was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested a threshold for rCBV that could help to establish the histopathological grade of adult gliomas and predict outcome, 6,12 but to date, no studies have been published on ependymomas. In the present study, the low number of grade-II patients compared with grade-III patients prevented us from investigating the difference between these grades, therefore we ran separate analyses of the differences between CEL and NEL.…”
Section: Discussionmentioning
confidence: 99%
“…Several prognostic factors influence the survival of patients with glioblastoma, including clinical characteristics (patient age, performance status), molecular characteristics (most notably, 06-methylguanine DNA methyltransferase promotor methylation, isocitrate dehydrogenase mutation, and deletion of the 1p and 19q chromosome arms [3]). Moreover, characteristics of noninvasive magnetic resonance (MR) imaging (most importantly, the apparent diffusion coefficient [ADC] derived from diffusion-weighted MR imaging and the relative cerebral blood volume [CBV] derived from perfusion-weighted MR imaging) also have been shown to be reliable prognostic biomarkers for stratification of patients with glioblastoma (4,5). More recently, the field of radiomics has been introduced to extend the noninvasive study of oncologic tissue beyond established MR imaging metrics, and a large number of quantitative descriptors that reflect textural variations in image intensity, among other features, have been derived from imaging data (6)(7)(8)(9)(10)(11).…”
Section: Author Contributionsmentioning
confidence: 99%